(untitled) (Journal of Economic Additions, 2020)
This paper aims to highlight sudan’s experience in financial innovation within the framework of Islamic banking, in light of the rapid developments in the financial markets at the global level, and focused on Sudan’s experience in issuing Government Islamic instruments as a model for financial innovation in Islamic Banking Framework. The paper concluded that government Islamic instruments in Sudan contributed to the diversification of liquidity management tools for the Sudanese banking system, increased bank financing and increased the volume of their trading on the Khartoum Stock Exchange. Keywords: Financial innovation; Islamic Banking; Sudan’s Experience; Government Islamic Instruments.